## How to solve order of operations w/missing number

Simple patterns, variables, the order of operations, simplification, evaluation, linear equations and graphs, etc.
sahmof2boys
Posts: 1
Joined: Wed Aug 15, 2012 2:10 am
Contact:

### How to solve order of operations w/missing number

Problem

76-?/2=41 Please explain the rule for solving these types of problems when there's a missing number. Thanks Is there a site that I can go to that will explain the step by step process on resolving these types of problems. I need help explaining these to my son who will be starting middle school in a few weeks. thanks in advance

stapel_eliz
Posts: 1628
Joined: Mon Dec 08, 2008 4:22 pm
Contact:
Problem: 76-?/2=41

Please explain the rule for solving these types of problems when there's a missing number.
To my knowledge, there is no "rule" or "formula". You just have to allow yourself enough time to plod through various possibilities until you happen upon a solution.

Grab some scratch paper, and have fun!

LoveMath
Posts: 7
Joined: Mon Sep 03, 2012 4:35 am
Contact:

### Re: How to solve order of operations w/missing number

You don't want to "plod through various possibilities until you happen upon a solution". That would take some time. You want to solve the problem by substituting the ? with an x. This gives:

(76-x)/2 = 41. Then the first thing to do is to get rid of the denominator. This can be done by multiplying both sides by 2. You then get
76-x = 41(2)
76-x = 82 Then by subtracting 76 from both sides gives
-x = 6 And now you multiply both sides by -1 in order to make x positive. That is,
-1(-x) = -1(6)
x = -6

This checks out since:
(76-(-6))/2 = (76+6)/2 = 82/2 = 41

MrAlgebra
Posts: 11
Joined: Tue May 24, 2011 7:36 pm
Location: NC
Contact:

### Re: How to solve order of operations w/missing number

With 76-?/2=41, you would write the equation out as 76 - x/2 = 41 and solve for x. Note that there are no parentheses around the 76 - x part, so the first thing you would be doing in the problem is dividing x by 2.

I would start out by subtracting 76 from both sides:

76 - x/2 = 41
76 - x/2 - 76 = 41 - 76
76 - 76 - x/2 = 41 - 76
- x/2 = -35

Now I would multiply both sides by -1 to get rid of the negatives.

-x/2 * -1 = -35 * -1
x/2 = 35

Now I would multiply both sides by 2 to get rid of the division by 2 on the left side of the equation.

x/2 * 2 = 35 * 2
x = 70

Now you should check your answer by putting 70 into the original equation to see if you get something that makes sense.

76 - ?/2 = 41
76 - 70/2 = 41
76 - 35 = 41
41 = 41